Semi-circular sweep voltammetry. Bio-analytical applications - Wang, Y; Compton, RG (Elsevier, 2021)
A novel voltammetric method applying a semi-circular potential sweep is applied to the simultaneous electroanalytical determination of solutions containing two components with similar oxidation potentials which precludes their resolution using conventional voltammetric methods including linear sweep, square wave and pulse voltammetries. Three such biologically important mixtures, ascorbic acid/acetaminophen, glucose/ethanol and hydroquinone/catechol were studied, analytical methods developed and the method of semi-circular sweep voltammetry shown to give notable advantages over the other conventional analytical voltammetries in terms of signal resolution and the sensitivity of the detection. Favourable accuracy was obtained using electrodes with either simple or no modification in the established linear detection ranges.